2018
DOI: 10.1111/ejn.13973
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous resting‐state gamma oscillations are not predictive of autistic traits in the general population

Abstract: The autism spectrum hypothesis states that not only diagnosed individuals but also individuals from the general population exhibit a certain amount of autistic traits. While this idea is supported by neuroimaging studies, there have been few electrophysiological studies. In particular, there have been no spontaneous resting‐state studies yet. In order to examine the autism spectrum hypothesis, the present study tried to predict the level of autistic traits typically developing young adults (n = 93) exhibit fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…In this sample, results suggested that gamma power was not related to the autistic quotient "AQ" score. This result may be due to the fact that autistic traits in the general population are not strong enough to be detected [65].…”
Section: Approach/avoidance Personality Traits and Eeg Gamma Rhythmmentioning
confidence: 96%
See 3 more Smart Citations
“…In this sample, results suggested that gamma power was not related to the autistic quotient "AQ" score. This result may be due to the fact that autistic traits in the general population are not strong enough to be detected [65].…”
Section: Approach/avoidance Personality Traits and Eeg Gamma Rhythmmentioning
confidence: 96%
“…The association between resting-EEG activity and FFFS, was considered in four articles [64,66,67,69], but, of these, only two studies found significative results [64,66]. Furthermore, one study considered the relation among EEG gamma activity and autistic traits [65], one article studied the role of resilience [68], and two articles found a positive association between EEG alpha activity and emotional intelligence [39,50]. Some studies have observed a significant relation between autistic traits and approach/avoidance personality traits [129], as well as emotional intelligence [130] and resilience [131].…”
Section: Approach/avoidance Personality Traits and Electrocortical Mementioning
confidence: 99%
See 2 more Smart Citations
“…Another neurodevelopmental condition oft‐linked with aberrant oscillatory functioning is autism (Murphy et al ., ), especially so in the gamma band (David et al ., ). In a sizeable cohort of young adults from the general population, De Groot & Van Strien () ask whether autism‐related traits in these ostensibly neurotypical individuals, might also be related to power across the gamma band. However, no such relationship was supported.…”
Section: The Role Of Neural Oscillations In Healthy and Disordered Comentioning
confidence: 99%